Analisis Pola dan Tantangan Usaha Mikro, Kecil, Dan Menengah (UMKM) dalam Adopsi Teknologi Blockchain di Era Industri 4.0 - Apol Pribadi Subriadi; Dimas Yuuki Achmad (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
In the era of Industry 4.0 marked by rapid digital technology advancement, Micro, Small, and Medium Enterprises (MSMEs) face unprecedented challenges and opportunities in their business transformation. Digital transformation has become imperative for the sustainability and growth of MSMEs amidst increasingly fierce global competition. This research aims to understand the readiness of MSMEs in adopting and leveraging digital technology, as well as to comprehend its impact on business performance and sustainability. This study employs a qualitative method with a phenomenological approach encompassing various aspects influencing MSMEs' digital transformation. Sample determination is conducted using snowball sampling technique, while data collection is carried out through in-depth interviews and document collection. Data analysis is performed using data source triangulation to identify key factors influencing MSMEs' readiness in facing the Industry 4.0 era. The findings of this research are expected to provide a deeper understanding of the current status and challenges faced by MSMEs in their digital transformation. Additionally, this study will also offer practical guidelines to enhance MSMEs' readiness, as well as policy recommendations that can assist MSMEs in adopting digital technology more effectively. The conclusions of this research are anticipated to contribute significantly to the development of MSMEs in the ever-changing and dynamic digital era.